Beyond immune escape: a variant surface glycoprotein causes suramin resistance in Trypanosoma brucei. Issue 1 (20th November 2017) - Wiedemar, Natalie; Graf, Fabrice E.; Zwyer, Michaela; Ndomba, Emiliana; Kunz Renggli, Christina; Cal, Monica; Schmidt, Remo S.; Wenzler, Tanja; Mäser, Pascal
Summary: Suramin is one of the first drugs developed in a medicinal chemistry program (Bayer, 1916), and it is still the treatment of choice for the hemolymphatic stage of African sleeping sickness caused by Trypanosoma brucei rhodesiense . Cellular uptake of suramin occurs by endocytosis, and reverse genetic studies with T . b . brucei have linked downregulation of the endocytic pathway to suramin resistance. Here we show that forward selection for suramin resistance in T . brucei spp. cultures is fast, highly reproducible and linked to antigenic variation. Bloodstream‐form trypanosomes are covered by a dense coat of variant surface glycoprotein (VSG), which protects them from their mammalian hosts' immune defenses. Each T . brucei genome contains over 2000 different VSG genes, but only one is expressed at a time. An expression switch to one particular VSG, termed VSG Sur, correlated with suramin resistance. Reintroduction of the originally expressed VSG gene in resistant T . brucei restored suramin susceptibility. This is the first report of a link between antigenic variation and drug resistance in African trypanosomes. Abstract : Suramin is still in use to treat sleeping sickness caused by Trypanosoma brucei rhodesiense . Here, we show that in culture, trypanosomes can quickly become suramin resistant by expressing one particular variant surface glycoprotein (VSG) gene, and they revert to sensitive upon replacement of that VSG gene with the originally expressed VSG gene. This is the first reported link between antigenic variation and drug resistance in African trypanosomes.